Reskript om fanatiske bøgers indførelse : 1700-tallets censurvirksomhed og kongens kamp mod ulydige boghandlere - Dimpker, Benedikte Xenia B.; Rieder, Ditte Johanne; Steensgaard, Benedikte Emilie T. (Kirkehistoriske Samlinger, 2025)
This article offers a transcription and analysis of a rescript issued by the Danish king Christian VI to booksellers in Copenhagen. Issued on 23 September 1740, the rescript ordered the booksellers to stop selling, printing, and importing separatist or fanatic books. Starting with an overview of the censorship in Denmark-Norway in the 1730-1740s, we cover how Christian VI made certain arrangements to protect the official church and his absolute power against separatist movements. We include two cases as examples on how censorship was done practically before the rescript was issued. In these cases, books were imported from foreign countries without consulting censorship authorities – even though there were clear legal restrictions concerning censorship in the Danish Law of 1683. These examples show that uncensored books were flourishing despite the legal restrictions. Thus, they might provide insight into the reasons for issuing the rescript – the booksellers needed a sharp reminder on the legal matters. We contend that the rescript is a product of its time and is an attempt to stop separatist movements from spreading in order to protect the state church and the power of the king. The rescript shows the importance and effect of literary (maybe even more so theological) works of the time. The king feared that separatist and fanatic thoughts could lead to unrest and disorder – in the worst case, this could lead the population into rebellion against the church and the king.